Phenotypic and Functional Profiles of Antigen-Specific CD4+ and CD8+ T Cells Associated With Infection Control in Patients With Cutaneous Leishmaniasis - Egui, Adriana; Ledesma, Darién; Pérez-Antón, Elena; Montoya, Andrés; Gómez, Inmaculada; Robledo, Sara María; Infante, Juan José; Vélez, Ivan Darío; López, Manuel C.; Thomas, M. Carmen (Frontiers in Cellular and Infection Microbiology, 2018)
Immunological host response is a key factor determining pathogenesis of cutaneous leishmaniasis. It is known that a Th1-cellular response is associated with infection control, and antigen-specific memory T cells are necessary for developing a quick and strong protective cellular response. The present manuscript reports the analysis of the functional and phenotypic profile of antigen-specific CD4+ and CD8+ T cells from cured patients who suffered cutaneous leishmaniasis (CL), patients with an active process of cutaneous leishmaniasis, asymptomatic individuals with positive Montenegro test and healthy donors (HD). Peripheral blood mononuclear cells (PBMC) from the patients exhibited a lymphoproliferative capacity after stimulation with total soluble proteins from Leishmania panamensis (SLpA) and Leishmania infantum (SLiA) and the recombinant paraflagellar rod protein-1 (rPFR1). Higher frequencies of antigen-specific TNAIVE cells were observed in asymptomatic and cured patients, mainly following stimulation with rPFR1, whilst T cells from patients with active cutaneous leishmaniasis showed a higher percentage of effector memory T cells (TEM for CD4+ T cells and TEMRA for CD8+ T cells). The amount of antigen-specific CD57+/CD8+ TEMRA cells from patients with active cutaneous leishmaniasis was higher than that in cured patients and asymptomatic subjects. Regarding functionality, an improved multifunctional CD8+ T cell response in cured patients versus those with active cutaneous leishmaniasis was detected. Moreover, cured patients also showed a significant increase in the frequency of cells expressing a Th1-type cytotoxic production profile (IFN-+/granzyme-B/+perforin+). The patients with an active leishmaniosis process had a significant higher frequency of CD8+ T cells expressing CD160 and 2B4 inhibitory receptors than that observed in cured patients. The expression profile observed in cured patients could be indicative of an imbalance towards the CD8+ Th1 response, which could be associated with infection control and, consequently, it could be a useful tool for facilitating the clinical follow-up of patients with cutaneous leishmaniasis. The results also suggest a possible exhaustion process of the CD8+ T cells associated with evolution of the Leishmania infection.